Diachronic Typology And The Reconstruction Of Non-Selective Interrogative Pronominals In Proto-Bantu - Idiatov, Dmitry (My University, 2022)
In this chapter, I propose a typologically informed reconstruction of the Bantu non-selective interrogative pronominals (NSIPs). Bantu NSIPs are characterised by a bewildering degree of formal variation, which makes their reconstruction particularly difficult. Therefore, I begin with a more general methodological discussion of the issue of variation in functional elements and the possible ways of dealing with it in reconstruction and by an overview of the diachronic typology of NSIPs. The most important results of the proposed reconstruction of Bantu NSIPs are that no human NSIP stem 'who?' can be reconstructed for Proto-Bantu (PB), while the morphological status of the non-human NSIP form 'what?' is ambiguous, and that the NSIP forms that can be reconstructed to PB were emerging out of complex interrogative constructions (viz. a clause-level cleft construction and a nominalisation construction) retained from some pre-PB stage within Southern Bantoid. Because of their complex constructional origin and the typical pathways of formal and semantic evolution, the reconstruction of interrogative pronominals bears significant relevance to the reconstruction of many other parts of Bantu morphosyntax, such as deictics (both spatial and discourse ones), the so-called augment and more generally referential status marking, nominalisation, noun classes, subject indexation, copulas, cleft constructions, relative clause constructions, constituent order, and root phonotactics (the question of vowel-initial roots and the identity of PB *j
Keywords: Proto-Bantu; Diachronic typology; Reconstruction